Scientific and practical matters of morphology in Al-Waseet Dictionary – A study of treating and representing them – - Omer, Abohaneefa OmerAlshareef Ali; Soliman, Mohamed Fawzy Fotouh; Alquhtani, Mohammed Abdullah Almazah (Journal of Humanities & Social Sciences, 2021)
This study tackles scientific & practical matters of morphology in Al-Waseet dictionary through the terminologies included in it as well as the linguistic approach to what was mentioned in the resources of morphology. Among the objectives of the research that it strived to achieve: standing with the morphological terms (scientific and practical) mentioned in Al-Waseet dictionary, as linked to the chapter in which they were studied, and identifying how to prove the morphological rule by presenting examples in Al-Waseet dictionary. The importance of the research lies in its presentation of a morphological issue in a lexical dictionary and linking it to what is mentioned in the books of morphology. As to the nature of the research, descriptive analytical research was followed, and the nature of the study required that it be on two points according to what was arranged in Al-Waseet dictionary “the empowered nouns and then the derived verbs” dealing with the main terms in the two sections. We have appended the morphological work to a conclusion in which the results of the research was illustrated. Of which: - That among the scientific morphological terms there is an overlap between the morphological study and the (Tajweed التجويد), which includes: (Alraum الرَّو), (Alishmamالإشما), and (Metigation التَّخفيف). - In morphological matters, a reference is made to dialects of the tribes, such as (Al imalaالإمالة) of "yaa" الياء" towards "Al-waw الواو" by Bain Asad. - There are morphological terms in scientific and practical fields that were not studied by the dictionary, including: "plural and substitution."